2011
DOI: 10.1111/j.1349-7006.2011.02061.x
|View full text |Cite
|
Sign up to set email alerts
|

MAFIP is a tumor suppressor in cervical cancer that inhibits activation of the nuclear factor‐kappa B pathway

Abstract: Cervical cancer is the second most common cancer in women. Inactivation of tumor suppressor genes underlies the transformation and progression of cervical cancer. Previously, we reported MAFIP can inhibit the growth of human cervical cancer HeLa cells. In this study, MAFIP was found to be downregulated in cervical intraepithelial neoplasia tissues. Induced expression of MAFIP in HeLa cells strongly inhibited tumor formation in nude mice, confirming its tumor suppressor activity in vivo. Overexpression of MAFIP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Activation of NF-κB through phosphorylation by the IKK complex (IKKα and IKKβ) and subsequent released from IκB in the cytoplasm, occur in the presence of TNFα as an activator, and is known as the canonical NF-κB pathway ( Garg and Aggarwal, 2002 ; Fitzgerald et al ., 2007 ). Inhibition of NF-κB results in apoptosis and suppression of tumor cell growth ( Li et al ., 2011 ; Olivera et al ., 2012 ; Sato et al ., 2011 ; Wilken et al ., 2011 ; Wu et al .,2011 ; Wu and Zhou, 2010 ; Kishida et al ., 2007 ; Oka et al ., 2007 ; Idris et al ., 2009 ; Moon et al ., 2009 ). Thus, this protein complex has been widely used as a key target for new anticancer drug discovery and development ( Garg and Aggarwal, 2002 ) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Activation of NF-κB through phosphorylation by the IKK complex (IKKα and IKKβ) and subsequent released from IκB in the cytoplasm, occur in the presence of TNFα as an activator, and is known as the canonical NF-κB pathway ( Garg and Aggarwal, 2002 ; Fitzgerald et al ., 2007 ). Inhibition of NF-κB results in apoptosis and suppression of tumor cell growth ( Li et al ., 2011 ; Olivera et al ., 2012 ; Sato et al ., 2011 ; Wilken et al ., 2011 ; Wu et al .,2011 ; Wu and Zhou, 2010 ; Kishida et al ., 2007 ; Oka et al ., 2007 ; Idris et al ., 2009 ; Moon et al ., 2009 ). Thus, this protein complex has been widely used as a key target for new anticancer drug discovery and development ( Garg and Aggarwal, 2002 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that inhibition of NF-κB activation induce apoptosis and suppress tumor growth ( Li et al ., 2011 ; Olivera et al ., 2012 ; Sato et al ., 2011 ; Wilken et al ., 2011. ; Wu and Zhou, 2010 ; Ahmad et al ., 2002 ; Kishida et al ., 2007 ; Oka et al ., 2007 ; Idris et al ., 2009 ; Moon et al ., 2009 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mRNA expression profile analysis has shown that MIP is expressed in human tissues such as liver, brain, kidney, heart and lung; but it is absent in skeletal muscle and pancreas tissues [2]. Compared with the corresponding normal tissues, the mRNA level of MIP is decreased significantly in some tumours [3]. MIP overexpression inhibits the growth and colony formation of human HCC cell line SMMC7721 [4].…”
Section: Introductionmentioning
confidence: 99%
“…MIP overexpression inhibits the growth and colony formation of human HCC cell line SMMC7721 [4]. Moreover, exogenous overexpression of MIP in Hela cells can inhibit tumour formation in nude mice [3]. Therefore, MIP is regarded as a candidate tumour suppressor protein.…”
Section: Introductionmentioning
confidence: 99%